A ROBOTIC PROSTHETIC A CONTROL SYSTEM AND A STRUCTURAL DIAGRAM DEVELOPMENT - Yevsieiev, Vladyslav; Maksymova, Svitlana; Starodubcev, Nikolaj (Collection of scientific papers «ΛΌГOΣ», 2022)
At the initial stage of prosthetic hand model design it is necessary to develop a structural diagram that will allow to consider the relationship and determine the principles of organization and work. To do this, it is proposed to use the classical approach to the development of automated feedback control systems [1], in our case, the control system will look as follows as shown in Figure 1.